Production and Logistics of Crossbow Bolts in the Early Renaissance. Florence and the War Against Lucca (1429–1433) - Picchianti, Simone (Tools of war, 2023)
In the autumn of 1429, Florence declared war on Lucca, to complete its domination over the north of Tuscany. The siege began in December and continued until the mercenary chief Niccolò Piccinino defeated the Florentine army outside the walls of Lucca, but the war continued until May 1433. In this period, although firearms already existed, the use of crossbows was still very important. To satisfy the requests of Florence, the men of Montefioralle, a small town in Chianti, specialised in the production of crossbow bolt heads. In this village of about two hundred inhabitants, every man was a blacksmith and together they produced on average 100,000 metal elements every six months. The shafts for the crossbow bolts were, on the other hand, produced by other specialised craftsmen in the mountains of the Casentino, and were assembled in other places. The Florentine war office, the Dieci di Balìa, took care of the logistics both to connect the different artisans and to send the ammunition to the battlefields and fortresses. Thanks to the documents kept in the State Archives of Florence, it has been possible to reconstruct the entire network of artisans, the management of shipments, and the quantity and expense for these ammunitions.